Specific Immunoglobulin E and G to Common Food Antigens and Increased Serum Zonulin in IBS Patients: A Single-Center Bulgarian Study - Milena Peruhova; Antoaneta Mihova; Iskra Altankova; Tsvetelina Velikova (Antibodies, 2022)
Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder whose pathogenesis is considered multifactorial, including abnormal gut motility, visceral hyperreactivity, psychological factors, disturbances in the brain-gut axis, leaky gut, oxidative stress, etc. We aimed to investigate serum levels of specific immunoglobulin E and G to common food antigens and zonulin and to assess their use in clinical practice for patients with IBS. Material and methods. We included 23 participants, 15 with IBS (diagnosed according to the Rome IV criteria) and 8 healthy controls. We investigated serum levels of specific IgG antibodies to 24 food antigens, specific IgE antibodies to 20 food antigens, anti-celiac antibodies, fecal calprotectin and serum zonulin by ELISA. Results. Food-specific positive IgG antibodies were significantly higher in patients with IBS than in controls (p = 0.007). IgE-mediated allergic reactions were found in five patients with IBS; no one had anti-TG antibodies. One-third of IBS patients demonstrated a low degree of chronic inflammation (positive fecal calprotectin test > 50 ng/mL) without specific bacterial infection. Serum levels of zonulin in IBS patients were higher than in healthy controls (0.378 ± 0.13 vs. 0.250 ± 0.14 ng/mL, p = 0.0315). However, no correlations between clinical symptoms and zonulin levels were found. Conclusion. The mechanisms of IgG hypersensitivity and low degree inflammation in IBS and elevated zonulin may contribute to multifactor pathogenesis in IBS.